Oxford handbook of thinking and reasoning / edited by Keith J. Holyoak and Robert G. Morrison - "Holyoak, Keith J. (ed.);Morrison, Robert G. (ed.)" (Oxford, 2012)
The Oxford Handbook of Thinking and Reasoning is a comprehensive and authoritative handbook covering all the core topics of the field of thinking and reasoning. Written by the foremost experts from cognitive psychology, cognitive science, and cognitive neuroscience, individual chapters summarize basic concepts and findings for a major topic, sketch its history, and give a sense of the directions in which research is currently heading. Chapters include introductions to foundational issues and methods of study in the field, as well as treatment of specific types of thinking and reasoning and their application in a broad range of fields including business, education, law, medicine, music, and science. The volume will be of interest to scholars and students working in developmental, social and clinical psychology, philosophy, economics, artificial intelligence, education, and linguistics.
Keywords: "Thought and thinking-Handbooks, Manuals etc"